How Social Norms and Social Identification Constrain Aggressive Reporting Behavior - Young, Donald (The Accounting Review, 2021)
ABSTRACT This study examines how the source and nature of reporting standards jointly influence compliance with those standards. More specifically, I examine how decision makers' identification with the source of the standards moderates compliance with different types of standards. Type refers to whether the accounting standard is descriptive or injunctive (i.e., prescriptive). Source refers to the entity promulgating the accounting standards. I conduct three experiments in which participants face a direct trade-off between reporting aggressively to maximize their personal wealth and reporting conservatively to adhere to a standard. I find that identification with the source causes less aggressive reporting for an injunctive standard, but when a standard is descriptive, identification has no effect or an opposite effect. When identification with the source is low, descriptive standards tend to work well compared to injunctive standards. With injunctive standards, persuasive factors, such as identification, likely influence financial managers' aggressive reporting behavior.